3=3(s+4)

Simple and best practice solution for 3=3(s+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=3(s+4) equation:


Simplifying
3 = 3(s + 4)

Reorder the terms:
3 = 3(4 + s)
3 = (4 * 3 + s * 3)
3 = (12 + 3s)

Solving
3 = 12 + 3s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-3s' to each side of the equation.
3 + -3s = 12 + 3s + -3s

Combine like terms: 3s + -3s = 0
3 + -3s = 12 + 0
3 + -3s = 12

Add '-3' to each side of the equation.
3 + -3 + -3s = 12 + -3

Combine like terms: 3 + -3 = 0
0 + -3s = 12 + -3
-3s = 12 + -3

Combine like terms: 12 + -3 = 9
-3s = 9

Divide each side by '-3'.
s = -3

Simplifying
s = -3

See similar equations:

| -63+12y+3=5(3y-5)-8 | | 20d+-4=16 | | a-3.2=55 | | -75=-5(5+2n) | | 7(c-2)+6=3+c-11 | | -3+12t=-7 | | 2(x+3)-4(3x-1)+6-(5x-2)+3x=0 | | 15=3+-3n | | 106=-8k+6 | | 0.40x+0.27y= | | .8y-8=.4+16 | | 4(8m-7n)+6(3n-4m)= | | 16x-31=33 | | 6(2n-4)=-72 | | 38.6+y=54.3 | | 5(3+6x)=285 | | 0.1x-2=11 | | 0.35x+0.35y= | | 2(x+3)=2x+12-6 | | 3r^2-9r+6= | | 19+15j+1=-19+6(4j-19) | | -16h+-1=15 | | -30=5b | | 4a+16+9= | | -4(4p+2)=-72 | | 5x+5=12.5 | | .5x+7=3x-8 | | -2(p-9)=0 | | 5*x*5=125 | | 0.20y-0.20x= | | -80=4(-6n+4) | | 30-14*2+8= |

Equations solver categories